Manajemen Berbasis Sekolah pada Pendidikan Agama Islam di Sekolah Menengah Atas Al-Mas’udiyah Semarang - Huda, Muhamad Alwi Maftuhul; Hamam, Hamam (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
School-based management offers schools the authority to manage institutions according to their abilities. This authority applies to managing all lines of school starting from resources, teaching staff and curriculum. This study aims to explain how Islamic religious education at SMA Al Mas`udiyyah Bandungan is based on the principles of school-based management. This research used descriptive qualitative method. Data were collected through interviews, documentation and observations on the research object. Based on the results of the research and discussion, it was concluded that (1) the independence of SMA Al Mas`udiyyah was implemented through the independence of curriculum development, independence in the procurement of educators and independence in facilities and infrastructure. (2) Participation in Islamic religious education occurs internally and externally. Internal that comes from school residents while external comes from the community, boarding schools and the government. (3) Openness at Al Mas'udiyyah High School is implemented through meetings with the community in the socialization of education programs and opening access to information for the community through the school committee or visiting the school directly.